Adsorption performance of synthesized basic bismuth nitrate and its titanium dioxide-silver modified systems for azo dye removal. - Ahmed Abdullah, Eshraq Ahmed (2011)
Effluents from industries contain large quantities of organic and inorganic pollutants. The high cost of activated carbon restricts its application in wastewater treatments. In addition, the low efficiency of low cost materials in removing organic contaminants from aqueous solution has resulted in a significant shift of attention towards synthesizing or developing new suitable adsorbents. Thus the present study was aimed to evaluate the potential use of basic bismuth nitrate compounds as new adsorbents for azo dye removal from aqueous solution. To achieve this aim, this study was divided into four stages. Firstly, the adsorbents were synthesized by precipitation method, calcined at 723K and characterized using different analytical techniques in order to gain further insights into the chemical environment of the adsorbents’ surface. Secondly, the adsorption performance of the adsorbents was evaluated using Methyl Orange (MO) and Sunset Yellow (SY) dyes as model pollutants. Thirdly, surface modification of the calcined adsorbent by addition of TiO2 and Ag was done in order to improve its adsorption performance. The reasons behind the adsorption enhancement were proposed. The dye adsorption mechanism onto the adsorbents was described using isotherm shape and the hydrophilichydrophobic character of the adsorbent surfaces. Finally, the desorption and reusability of the adsorbents were evaluated. TGA and XRD analyses indicated that the synthesized sample, Bi6O4(OH)4(NO3)6.7H2O (BBN) was converted to Bi5O7NO3 upon calcination at 723K. The addition of TiO2 and AgNO3 had resulted in the formation of TiO2/Ag–i6O6(OH)2(NO3)4.1.5H2O (PTBA0.5) which was then converted to TiO2/Ag– Bi5O7NO3 (TBA0.5) upon calcination. The presence of water, nitrate, hydroxyl group and octahedral TiO2 (for TiO2/Ag modified sample) were confirmed by FTIR and XPS spectra. TEM images and XRD analysis indicated that the TiO2 particles were only deposited on the surface of the modified adsorbent. The adsorption of dyes onto the adsorbents was found to be highly dependent on the adsorbent dose, initial concentration of dye and temperature. The presence of H+ and OH-; however, only played an important role in the adsorption process onto the calcined adsorbents. The uncalcined adsorbents demonstrated a better ability to remove methyl orange and sunset yellow dyes with shorter equilibrium time compared to that of calcined adsorbents. The high adsorption capacities of uncalcined adsorbent basic bismuth nitrate, BBN, could be attributed to its lower pHpzc and surface area. The TiO2/Ag modified adsorbent also showed higher adsorption capacities compared to the unmodified adsorbents. The enhancement in the adsorption performance could be attributed to the increase in the hydrophilic character of the adsorbent which in turn increase the electrostatic attraction with the anionic dye molecules. Other than that, effect of pore volume of modified adsorbents may produce a better environment for adsorption of the dye molecules. The adsorption kinetics of azo dye onto uncalcined adsorbents obeyed the pseudosecond order reaction, indicating that the removal behaviour might be preceded via chemisorption mechanism. Although intra-particle diffusion could only be the rate limiting step of uptake behaviour at a certain stage, the film diffusion had a significant contribution on dye adsorption onto uncalcined sample. However, firstorder and Langmuir 1,2–mixed order kinetics reaction gave the best description of azo dye adsorption onto calcined adsorbents. The maximum adsorption capacities for complete monolayer coverage were 35.7,55.6, 15.9, and 26.3 mg g-1 for methyl orange dye adsorption onto BBN, PTBA0.5,Bi5O7NO3 and TBA0.5, respectively. The estimated values of sunset yellow dye removal were 25.6 and 31.3 mg g-1 for BBN and PTBA0.5, respectively, and 23.3 mg g-1 for TBA0.5, which sufficiently good compared to some synthesized adsorbents derived from low-cost materials. The adsorption efficiencies were 9.66 , 26.98 , 30.39 and 20.6 mmol nm-2 for methyl orange dye adsorption onto BBN, PTBA0.5, Bi5O7NO3 and TBA0.5, respectively. The estimated values of sunset yellow dye removal were 5.01 and 10.99mmol nm-2 for BBN and PTBA0.5, respectively, and 13.2 mmol nm-2 for TBA0.5. These values are more than the reported values for porous carbon suggesting the potential use of basic bismuth nitrate adsorbents in wastewater treatments. Overall, the prepared materials can be effectively used as new dsorbents for organic pollutant removal.